Indoor/outdoor relationships of size-resolved particle concentrations in naturally ventilated school environments - Tippayawong N. (2014)
Assessment of indoor air quality in typical classrooms is vital to students' health and their performance. The present study was designed to monitor indoor and outdoor size-resolved particle concentrations in a naturally ventilated classroom and investigate factors influencing their levels and relationships. The experiments were performed, at normal ventilation condition with doors and windows opened, on the top floor of a public school building near a busy commercial area of Chiang Mai, Thailand. The particle number concentrations were measured using an optical counter with four size intervals between 0.3 and 5.0 μm. The dataset was collected during weekdays and weekends with a 24 h sampling period over November and December 2005. It was observed that the median indoor particle number concentrations during daytime for 0.3-0.5, 0.5-1.0, 1.0-2.5, and 2.5-5.0 μm size intervals were about 1.6×108, 1.7×107, 1.2×106, and 4.1×105 particles/m3, respectively. It was also found that concentrations at weekends were slightly higher those measured on weekdays, and at night, appeared to be higher than daytime. Indoor particles were observed to exhibit similar temporal variation pattern with outdoor particles. Results suggested that a significant contribution to indoor particles was from penetration of outdoor particles, whereas indoor sources generated from occupant activity did not show strong evidence. High outdoor particle loading and high air exchange rate were thought to be predominant causes. Ratios of indoor-to-outdoor (I/O) particle concentrations varied in a relatively narrow range from 0.69 to 0.88 with average values well below 1. The I/O ratios were in the range from 0.74 to 0.88 for submicrometer particles and from 0.69 to 0.80 for supermicrometer particles. © 2008 Elsevier Ltd. All rights reserved.